Fiscal Correction Analysis of Commercial Profit and Loss Report at Money Changer Company - Haryono, Selly Anggraeni; Puspanita, Intan (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to analyze the fiscal corrections on commercial loss profit report in determining corporate income tax at PT MCA, a money changer company. The research method used in this study is the descriptive qualitative method, with data collection methods carried out through interviews and documentation. The results of this study are the company has applied the tax regulation for preparing the fiscal correction and calculate the corporate income tax. For this fiscal year 2021, the company obtained the fiscal loss amounting to 1.24 billion rupiah, a decrease of 396 million rupiah from the company’s commercial profit and loss report. Due to the company obtained the fiscal loss, the company did not have obligation to pay corporate income taxes, however the calculation of estimated tax losses for the year ended December 31, 2021 was the basis for preparing annual tax return (SPT) for 2021.